1985
DOI: 10.1073/pnas.82.23.7884
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal sequence of p36 and associated p10: identification of the site of tyrosine phosphorylation and homology with S-100.

Abstract: ABSTRACTp36 is a major substrate of both viral and growth factor-receptor-associated tyrosine protein kinases. p36 can be isolated as a complex consisting of a subunit of Mr 36,000 (p36) and a subunit ofMr 10,000 (p10), and it represents an abundant cellular protein. We have isolated the p36-plO complex from bovine intestinal epithelium and analyzed the amino terminus of both subunits. Sequence analysis of the first 56 amino acids of p1O demonstrates a striking sequence homology (48% identically placed residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
152
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(158 citation statements)
references
References 31 publications
6
152
0
Order By: Relevance
“…The NH2-terminal tails of the annexins are quite variable in sequence and length. In p36 (annexin II), this region contains both serine and tyrosine phosphorylation sites (Glenney & Tack, 1985;Gerke, 1989) and p36 has been shown to be a substrate for pp6Ov-src (Huang et al, 1986;Erikson et al, 1984;Saris et al, 1986) and protein kinase C (Gould et al, 1986;Barnes et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH2-terminal tails of the annexins are quite variable in sequence and length. In p36 (annexin II), this region contains both serine and tyrosine phosphorylation sites (Glenney & Tack, 1985;Gerke, 1989) and p36 has been shown to be a substrate for pp6Ov-src (Huang et al, 1986;Erikson et al, 1984;Saris et al, 1986) and protein kinase C (Gould et al, 1986;Barnes et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…p36 exists as either a monomer or as a heterotetramer with an 11 kDa protein, pll, forming a (p36)2(p1l)2 complex (Erikson et al, 1984;Glenney & Tack, 1985;Johnsson et al, 1988;Glenney et al, 1986;Zokas & Glenney, 1987). In the latter form, it may be a structural component of the cytoskeletal framework.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in function between the ERM proteins and AIIt, and the presence of the F-actin binding domain within the C terminus of the ERM proteins, led us to suspect that the C-terminal region of the annexin II subunit of AIIt might be involved in F-actin binding. It is known that the N terminus of annexin II is responsible for binding of p11 (23,46,47), however, a role has not been attributed to the C-terminal region of the protein. Therefore, we have used site-directed mutagenesis to truncate the C terminus of annexin II to assess its possible function in F-actin binding.…”
Section: Discussionmentioning
confidence: 99%
“…growth factor and platelet-derived growth factor, annexin 2 is phosphorylated on a tyrosine as well as on a serine (Isacke et a!., 1986). The serine residue was identified as Ser25 within the amino-terminal region (Glenney and Tack, 1985). Alternatively, in vitro phosphorylations of annexin 2 with calmodulin-dependent protein kinase, cyclic AMP-dependent protein kinase, and protein kinase C indicated that the monomeric heavy chain is a much better substrate than the complex (Johnsson et al, 1986); these studies showed also the presence of a second site phosphorylated by protein kinase C, probably Ser°.…”
mentioning
confidence: 90%